2018
DOI: 10.3390/molecules23092267
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotides Targeting Telomeres and Telomerase in Cancer

Abstract: Telomeres and telomerase have become attractive targets for the development of anticancer therapeutics due to their involvement in cancer cell immortality. Currently, several therapeutics have been developed that directly target telomerase and telomeres, such as telomerase inhibitors and G-quadruplex stabilizing ligands. Telomere-specific oligonucleotides that reduce telomerase activity and disrupt telomere architecture are also in development as novel anticancer therapeutics. Specifically, GRN163L and T-oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 87 publications
(173 reference statements)
0
50
0
Order By: Relevance
“…Telomeres are also targeted using guanine-rich oligonucleotide (GRO) homologous to the 3 single-stranded overhang, known as T-oligos, a specific 11-base oligonucleotide sequence, (5 GTTAGGGTTAG), which accumulates in the nucleus and induces DDR with minimal or no functional effect on normal cells [250,253]. Treatment with T-oligos in vitro has been shown to be effective in reducing viability and tumor growth in several cancers, including melanoma, prostate, ovarian, lung, breast, and colorectal cancer [250,[254][255][256][257][258]. T-oligos are hypothesized to interfere with normal telomeric structure and form G-quadruplexes, inducing genomic stress in addition to aberrant upregulation of DDR pathways, and TRF2 and POT1 have shown to be upregulated after T-oligo treatment [250,254,259].…”
Section: Telomeres As Potential Targets For Anti-cancer Therapymentioning
confidence: 99%
“…Telomeres are also targeted using guanine-rich oligonucleotide (GRO) homologous to the 3 single-stranded overhang, known as T-oligos, a specific 11-base oligonucleotide sequence, (5 GTTAGGGTTAG), which accumulates in the nucleus and induces DDR with minimal or no functional effect on normal cells [250,253]. Treatment with T-oligos in vitro has been shown to be effective in reducing viability and tumor growth in several cancers, including melanoma, prostate, ovarian, lung, breast, and colorectal cancer [250,[254][255][256][257][258]. T-oligos are hypothesized to interfere with normal telomeric structure and form G-quadruplexes, inducing genomic stress in addition to aberrant upregulation of DDR pathways, and TRF2 and POT1 have shown to be upregulated after T-oligo treatment [250,254,259].…”
Section: Telomeres As Potential Targets For Anti-cancer Therapymentioning
confidence: 99%
“…The BFB cycle was reported to be associated with CIN development and peri-centromeric instability in MM (Sawyer et al, 2009). The most promising drug to specifically target telomerase is GRN163L, a synthetic lipid-conjugated 13-mer N3→P5 thio-phosphoramidate deoxyribo-oligonucleotide that blocks the template zone of telomerase and has potential antineoplastic activity (Schrank et al, 2018) (Figure 1). A study using myeloma cell lines found that prominent inhibition of telomerase activity with GRN1613L led to a reduction in viability to < 5% of baseline levels over a period of three to 5 weeks (Shammas et al, 2008) (Table 1).…”
Section: Telomerase Inhibitorsmentioning
confidence: 99%
“…In addition, there are few studies on the mechanisms of T‐oligo in ALT cancer cells. In 2018, T‐oligo was extensively reviewed by Schrank et al, and therefore, we will not repeat it in this review …”
Section: Oligonucleotides Targeting Telomeres and Telomerasementioning
confidence: 99%